2014
DOI: 10.1186/1742-2094-11-63
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 impedes Schwann cell-mediated myelination

Abstract: BackgroundPro-inflammatory cytokines are known to have deleterious effects on Schwann cells (SCs). Interleukin 17 (IL-17) is a potent pro-inflammatory cytokine that exhibits relevant effects during inflammation in the peripheral nervous system (PNS), and IL-17-secreting cells have been reported within the endoneurium in proximity to the SCs.MethodsHere, we analyzed the effects of IL-17 on myelination and the immunological properties of SCs. Dorsal root ganglia (DRG) co-cultures containing neurons and SCs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 68 publications
(79 reference statements)
0
15
0
2
Order By: Relevance
“…Moreover, in an inflammation/ injury model, where peripheral neuropathy was induced in C57BL/6 mice by partial ligation of the sciatic nerve, mice lacking IL-17 had significantly fewer infiltrating T cells and macrophages and decreased pain hypersensitivity (36). Moreover, IL-17 may have direct effects on Schwann cells, through inhibition of myelination and upregulation of MHC-I (37). Further studies are needed to determine whether both IFN-γ and IL-17 play critical roles in the immunopathology of CIDP.…”
Section: Immune Effectors In Cidpmentioning
confidence: 99%
“…Moreover, in an inflammation/ injury model, where peripheral neuropathy was induced in C57BL/6 mice by partial ligation of the sciatic nerve, mice lacking IL-17 had significantly fewer infiltrating T cells and macrophages and decreased pain hypersensitivity (36). Moreover, IL-17 may have direct effects on Schwann cells, through inhibition of myelination and upregulation of MHC-I (37). Further studies are needed to determine whether both IFN-γ and IL-17 play critical roles in the immunopathology of CIDP.…”
Section: Immune Effectors In Cidpmentioning
confidence: 99%
“…IFN-γ serves many functions in rejection, such as maintaining T cell survival, inducing MHC expression in nearby cells and inducing macrophages to produce pro-inflammatory cytokines and ROS (33). IL-17 is produced by Th17 cells and stimulates proinflammatory cytokine production, antigen presentation, and may suppress myelin production in Schwann cells (34). We observed that PEG-fused PNAs exhibit significant downregulation of each of these critical cytokines, as well as effector molecules FASL, PRF1, and GZMB that are commonly employed by cytotoxic T cells to kill donor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, FN-CS1 mediates T cell adhesion, migration, and rolling along myelinated fibers [ 25 28 , 52 – 54 ], which through secretion of algesic IL-17A [ 13 ] helps sustain the adaptive immune response and the persistent state of mechanical allodynia. At the later stage post-nerve damage, IL-17A release from Th17 cells may help sustain mechanical hypersensitivity by impeding Schwann-cell-mediated remyelination of sensory neurons [ 55 ].…”
Section: Discussionmentioning
confidence: 99%